Analisis Laporan Keuangan Perbandingan Kinerja Keuangan Perusahaan Manufaktur di Indonesia : Studi Pada PT Beton Jaya Manunggal Tbk PT Pelat Timah Nusantara Tbk Dan PT Tembaga Mulia Semanan Tbk Periode 2019-2023 - Sukma Asri; Reinatto Yakobus Pati Agon Atakelan; Celine Amanda Sarifatul Sabrina; Cholis Hidayati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study analyzes the comparative financial performance of three metal sub-sector manufacturing companies listed on the Indonesia Stock Exchange, namely PT Beton Jaya Manunggal Tbk, PT Pelat Timah Nusantara Tbk, and PT Tembaga Mulia Semanan Tbk, during the period 2019–2023. The study uses a descriptive qualitative method with a comparative approach to evaluate financial ratios such as liquidity, solvency, activity, profitability, and market. The results show that PT Beton Jaya Manunggal Tbk excels in liquidity and solvency ratios, reflecting short-term financial stability and low dependence on debt. PT Tembaga Mulia Semanan Tbk shows the best performance in activity efficiency, with high asset turnover and optimal receivables management. Meanwhile, PT Pelat Timah Nusantara Tbk has the highest profitability ratio, reflecting the effectiveness of its equity strategy in generating profits. This study provides in-depth insight into the dynamics of the financial performance of the manufacturing sector in Indonesia, identifies effective financial strategies, and underlines the need to adapt to external challenges such as fluctuations in raw material prices and the impact of the COVID-19 pandemic.